Food Microbiology. - Adams, M. R.; Moss, M. O. (Royal Society of Chemistry, The Springer [distributor], 2007)
Annotation This is the third edition of a widely acclaimed text which covers the whole field of modern food microbiology. It has been thoroughly revised and updated to include the most recent developments in the field. It covers the three main aspects of the interaction between micro-organisms and food - spoilage, foodborne illness and fermentation - and the positive and negative features that result. It discusses the factors affecting the presence of micro-organisms in foods and their capacity to survive and grow.
Keywords: Food -- Microbiology.; Microbial ecology.; Microbiology.; Pollution.; Food industry and trade.; Public health.; Industries.; Biology.; Medical care.; Life sciences.; Physical sciences.; Food science.; elektronické knihy; electronic books